The role of electronic accounting information systems on the quality of financial reports in Palestinian governmental institutions - ABDELLAH SHAQFA, KHALIL IBRAHIM (Journal of Research in Finance and Accounting, 2020)
The objectives of the study were to measure the role of electronic accounting information systems in improving the quality of financial reports for Palestinian government institutions, and to achieve the goals of the study the researcher adopted the descriptive analytical approach and the study tool was represented by a questionnaire distributed to the entire study community of users of the systems and their outputs, and the researcher has reached results, the most important of which are reports The financial statements issued by the electronic accounting information systems in the Palestinian government institutions are neutral and representative of facts and events according to legal controls and professional standards and they enable decision-makers to differentiate between the beginners It supports appropriate decision making. The researcher has recommended the need to develop electronic accounting information systems and work to increase the efficiency and speed of accounting treatments, while requiring government institutions to apply them to ensure access to financial reports in accordance with legal controls, while providing a stable legal and administrative environment compatible with the application of electronic accounting information systems.